2014
DOI: 10.1007/s10641-014-0351-7
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurring bighead and silver carps show similar food preference but different isotopic niche overlap in different lakes

Abstract: Silver carp (Hypophthalmichthys molitrix) and bighead carp (Hypophthalmichthys nobilis) are among the most important fish species in aquaculture and have been introduced to many countries. The feeding ecology of these filter-feeding cyprinids is not well understood and has been mostly based on gut content analyses. We analyzed δ 13 C and δ 15 N stable isotope ratios of food resources and fish muscle tissues in four Chinese lakes, where these two species co-occur. Data analysis through Bayesian mixing models re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 76 publications
(116 reference statements)
0
6
0
Order By: Relevance
“…Hence, for fish >40 cm, muscle tissue SI values can better represent their long dietary periods. Jayasinghe et al (2015) indicated that SC is more likely a phytoplankton feeder, while BC is more likely a zooplankton feeder. However, the categories that we used to classify food types would not result in either a phytoplankton-only feeder or zooplankton-only feeder, because both plankton types consisted of species with a wider range in body sizes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Hence, for fish >40 cm, muscle tissue SI values can better represent their long dietary periods. Jayasinghe et al (2015) indicated that SC is more likely a phytoplankton feeder, while BC is more likely a zooplankton feeder. However, the categories that we used to classify food types would not result in either a phytoplankton-only feeder or zooplankton-only feeder, because both plankton types consisted of species with a wider range in body sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Although both species utilize the suspending particle resources, they can coexist by regulating their proportions of these particles and the trophic level. Jayasinghe et al (2015) pointed out that co-occurring SC and BC showed similar food preference but a different isotopic niche overlap in different lakes with variation of resource availability. In our study, we found that in order to coexist, BC occupied a larger isotopic niche overlap in the Nianyushan Reservoir in our study, possibly because they had to live when differences in relative survival ability were small.…”
Section: Resources Utilization and Coexistencementioning
confidence: 99%
See 3 more Smart Citations